Comparison of energy expenditure measurements by a new basic respiratory room vs. classical ventilated hood - Timia Van Soom; Wiebren Tjalma; Ulrike Van Daele; Nick Gebruers; Eric van Breda (Nutrition Journal, 2023)
Abstract Background Nutritional support is often based on predicted resting energy expenditure (REE). In patients, predictions seem invalid. Indirect calorimetry is the gold standard for measuring EE. For assessments over longer periods (up to days), room calorimeters are used. Their design makes their use cumbersome, and warrants improvements to increase utility. Current study aims to compare data on momentary EE, obtained by a basic respiration room vs. classical ventilated hood. The objective is to compare results of the basic room and to determine its 1)reliability for measuring EE and 2)sensitivity for minute changes in activity. Methods Two protocols (P1; P2)(n = 62; 25 men/37 women) were applied. When measured by hood, participants in both protocols were in complete rest (supine position). When assessed by room, participants in P1 were instructed to stay half-seated while performing light desk work; in P2 participants were in complete rest mimicking hood conditions. The Omnical calorimeter operated both modalities. Following data were collected/calculated: Oxygen uptake ( $$\dot{V}$$ V ˙ O2(ml/min)), carbon dioxide production ( $$\dot{V}$$ V ˙ CO2ml/min), 24h_EE (kcal/min), and respiratory exchange ratio (RER). Statistical analyses were done between modalities and between protocols. The agreement between 24h_EE, $$\dot{V}$$ V ˙ O2 and $$\dot{V}$$ V ˙ CO2 obtained by both modalities was investigated by linear regression. Reliability analysis on 24h_EE determined ICC. Results No significant differences were found for 24h_EE and $$\dot{V}$$ V ˙ O2. $$\dot{V}$$ V ˙ CO2 significantly differed in P1 + P2, and P2 (hood > room). RER was significantly different (hood > room) for P1 + P2 and both protocols individually. Reliability of 24h_EE between modalities was high. Modality-specific results were not different between protocols. Discussion/conclusion The room is valid for assessing momentary EE. Minute changes in activity lead to a non-significant increase in EE and significant increase in RER. The significant difference in $$\dot{V}$$ V ˙ CO2 for hood might be related to perceived comfort. More research is necessary on determinants of RER, type (intensity) of activity, and restlessness. The design of the room facilitates metabolic measurements in research, with promising results for future clinical use.